Reading assessment linking language, literacy, and cognition - Farrall, Melissa Lee (John Wiley and Sons, Inc., 2012)
"This accessible, friendly guide is the first of its kind to present a research-based, integrated review of reading, cognition, and oral language testing and assessment. The theoretical underpinnings of reading, language, and literacy are covered, as well as detailed information and administration tips on the myriad reading inventories that may be used in a reading psychoeducational assessment. Unique in its inclusion of instruction on crafting professional evaluation reports to illuminate a student's strengths and weaknesses, this inviting book will enable school psychologists, reading specialists, and learning disabilities specialists to conduct effective interdisciplinary remedial recommendations and interventions"--